Investigation of Dielectric, Magnetic and Electrical Behavior of BFO/GNPs Nano-Composites Synthesized via Sol-Gel Method - Nageena, Arsa; Manzoor, Alina; Muhammad Afzal, Amir; Arshad, Muhammad Imran; Shahzad, Aamir; Kashif, Muhammad (Journal of Materials and Physical Sciences, 2022)
Nano composites of Ba0.5Bi0.5Nd0.05Fe0.95O3 multiferroic with graphene nano platelets (GNPs)x (x = 0, 0.125 %, 0.375 %, and 0.5 %) were synthesized using sol-gel auto ignition process. XRD analysis revealed a single rhombohedrally distorted phase of Ba0.5Bi0.5Nd0.05Fe0.95O3. The present study unfold the impact of GNPs on the structural, electrical, dielectric, and magnetic properties of Ba0.5Bi0.5Nd0.05Fe0.95O3 multiferroics. The substitution of Rare earth elements in pure BFO reduced the value of leakage current which is the basic drawback related with pure BFO. The prepared nanocomposites are then sintered at 800 °C for 7 hrs. The X-ray diffraction patterns showed the rhombohedral distorted perovskite crystal structure of the prepared samples including lattice constant, crystallite size, and X-ray density. The average crystallite sizes of the prepared nanocomposites are noticed in the range 28.14 -to 29.74 nm with increasing the GNPs concentration and lattice constant is found in the range 11.59 -to 11.61 Å. Temperature-dependent resistivity is first observed to increase with an increase in temperature then resistivity decreased with increasing the temperature which indicates a semi-conductor-like behavior as measured by two probe I-V characteristics. LCR technique showed that both the dielectric constant and the dissipation factor are decreased with an increase in frequency. VSM results indicated that saturation magnetization is noted to increase while remanent magnetization decreases with increasing concentration of GNPs.